Dexmedetomidine as an adjuvant to Nalbuphine in patient controlled analgesia for post-operative pain in Laparoscopic Cholecystectomy: A preliminary study - Nabaweya M Kamal; Tarek A Radwan; Ahmed A Mohamed; Maha abdelbar; Ahmed M Abdelaziz Hassan; Magdy M Elsebae; Shady A AbdElmoneem (Global Journal of Anesthesiology - Peertechz Publications, 2019)
Postoperative pain control is an important factor affecting patient recovery, return to normal bowel movement, ambulation and daily activity. Intravenous patient-controlled analgesia (IV-PCA) which allows the patient to administer his own pain relief is considered as an efficient tool to control postoperative pain. Safety of IV-PCA relies on the concept of negative feedback control system so that the patient will become too sedated to physically push the button to receive more opioid before reaching a critical point of severe respiratory depression [1].